Phytoliths as a Tool for the Identification of Some Chloridoideae Grasses in Kerala. (23rd December 2012) - Jattisha, P. I.; Sabu, M.
Abstract : The phytoliths of eight genera including fifteen species of grasses under the subfamily Chloridoideae in Kerala were studied. Phytoliths were studied after chemical isolation. Every species was found to produce a diverse array of phytoliths. However the frequency assemblages of phytoliths, their size, and orientation in the epidermal layer appear to vary among the different species and hence can be used for the delimitation of the taxa. Consequently, an identification key following the International Code for Phytolith Nomenclature was developed for all the species studied.